Evidence-based management of stroke - Biller, Jose; Ferro, Jose M. (tfm Pub., 2011)
The purpose of this book is to review that evidence, for both medical and surgical therapies as well as preventative strategies, drawing on the expertise of leading international authorities to distinguish the issues for which there is a consensus on best practice from those for which the evidence remains inconclusive.